Relación músculo-hueso en ratones de una población segregante discriminados por sus patrones de crecimiento en peso corporal y longitud caudal - Pippa, C. (2013)
According to Hooper´s hypothesis the growth plate acts as a pacemaker to set the pace of skeletal and muscle growth in a sequence that affects the longitudinal growth of bone, muscle mass and the weight of the bone. Its adequacy for characterizing the muscle-bone relationship in the mouse was studied in male (n=326) and female (n=332) mice belonging to a segregating population derived from a cross between two lines selected for body conformation with significant differences in total biomass supported but not in the length of their femurs. Mice were discriminated by their dynamic patterns of skeletal (tail length) growth and biomass (body weight) deposition characterized by the asymptotic size and maturation rate values estimated by the Gompertz function. The behavior of five indicators of muscle-bone relationship: femur and tibia weight, femur and tibia length and triceps surae muscle weight was studied. Regarding both, body weight and skeletal length growth patterns, the results corroborate the role of pacemaker on muscle and skeletal growth proposed forthe epiphyseal plate by Hooper´s hypothesis.